Anti-adhesion Gel versus No gel following Operative Hysteroscopy prior to Subsequent fertility Treatment or timed InterCourse (AGNOHSTIC), a randomised controlled trial: protocol. Issue 1 (16th February 2021) - van Wessel, S; Hamerlynck, T; Schutyser, V; Tomassetti, C; Wyns, C; Nisolle, M; Verguts, J; Colman, R; Weyers, S; Bosteels, J
Abstract: STUDY QUESTIONS: Does the application of anti-adhesion gel, compared to no gel, following operative hysteroscopy to treat intrauterine pathology in women wishing to conceive increase the chance of conception leading to live birth? WHAT IS KNOWN ALREADY: Intrauterine adhesions (IUAs) following operative hysteroscopy may impair reproductive success in women of reproductive age. Anti-adhesion barrier gels may decrease the occurrence of IUAs, but the evidence on their effectiveness to improve reproductive outcomes is sparse and of low quality. STUDY DESIGN, SIZE, DURATION: This multicentre, parallel group, superiority, blinded and pragmatic randomised controlled trial is being carried out in seven participating centres in Belgium. Recruitment started in April 2019. Women will be randomly allocated to treatment with anti-adhesion gel (intervention group) or no gel (control group). Sterile ultrasound gel will be applied into the vagina as a mock-procedure in both treatment arms. The patient, fertility physician and gynaecologist performing the second-look hysteroscopy are unaware of the allocated treatment. Power analysis, based on a target improvement of 15% in conception leading to live birth using anti-adhesion gel, a power of 85%, a significance level of 5%, and a drop-out rate of 10%, yielded a number of 444 patients to be randomised. The baseline rate of conception leading to live birth in the control group is expected to be 45%. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women of reproductive age (18–47 years), wishing to conceive (spontaneously or by fertility treatment) and scheduled for operative hysteroscopy to treat intrauterine pathology (endometrial polyps, myomas with uterine cavity deformation, uterine septa, IUAs or retained products of conception) are eligible for recruitment. Women may try to conceive from 3 to 6 weeks after receiving allocated treatment with follow-up ending at 30 weeks after treatment. If the woman fails to conceive within this timeframe, a second-look hysteroscopy will be scheduled within 2–6 weeks to check for IUAs. The primary endpoint is conception leading to live birth, measured at 30 weeks after randomisation. The secondary endpoints are time to conception, clinical pregnancy, miscarriage and ectopic pregnancy rates, measured at 30 weeks after receiving allocated treatment. The long-term follow-up starts when the patient is pregnant and she will be contacted every trimester. STUDY FUNDING/COMPETING INTEREST(S): This work is funded by the Belgian Healthcare Knowledge Centre (KCE). The anti-adhesion gel is supplied at no cost by Nordic Pharma and without conditions. Dr. Tomassetti reports grants and non-financial support from Merck SA, non-financial support from Ferring SA, personal fees and non-financial support from Gedeon-Richter, outside the submitted work. None of the other authors have a conflict of interest.